Magnesium oxide thermochemical heat storage material and preparation method thereof
By accurately controlling the reaction temperature, time and calcining atmosphere, a nano-scale structured magnesium oxide thermal chemical storage material was prepared, which solved the problem of slow reaction rate of the MgO/MgCO3 system and achieved efficient thermal energy storage and release.
Patent Information
- Application Number
- CN202411972163.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
As a solid-phase heat storage material, the MgO/MgCO3 system has a slow reaction rate, which limits its application in industrial large-scale production and applications.
By accurately controlling the reaction temperature and time of magnesium salt solution and carbonate solution, and controlling the calcining atmosphere, a nano-scale structure of magnesium oxide thermochemical heat storage material is prepared to increase its heat storage capacity.
The thermal energy release and storage rate of magnesium oxide heat storage materials is improved, the contact area between CO2 and MgO is enhanced, the reaction rate is improved, and a higher energy storage density is achieved.
Smart Images

Figure CN119898802A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium oxide energy storage, and in particular relates to a magnesium oxide thermochemical heat storage material and a preparation method thereof. Background Art
[0002] Solid magnesium oxide thermochemical heat storage material is a new type of material that can efficiently store and release thermal energy. It has many advantages, such as high energy storage density, long-term stability and pollution-free, so it is widely used in renewable energy storage systems and thermal management. Among them, the low-cost, wide temperature window, high heat storage density and environmentally friendly MgO / MgCO3 system thermochemical heat storage material is considered to be one of the most promising materials.
[0003] MgO(s)+CO2(g)=MgCO3(s)ΔH=-116.4k J / mol
[0004] However, as a solid-phase heat storage material, the MgO / MgCO3 system is also limited by the slow reaction rate factor, which is not conducive to large-scale industrial production and application. Summary of the invention
[0005] In view of the above problems, the present invention provides a magnesium oxide thermochemical heat storage material and a preparation method thereof. By precisely controlling the reaction process and calcination atmosphere, a heat storage material with a special nanoscale structure is prepared to increase the heat storage capacity of the magnesium oxide heat storage material.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] A method for preparing a magnesium oxide thermochemical heat storage material comprises the following steps:
[0008] S1: weigh magnesium salt and carbonate, and add deionized water to dissolve them respectively to form a magnesium salt solution and a carbonate solution;
[0009] S2: adding the magnesium salt solution to the magnesium carbonate solution, and controlling the reaction temperature to be 30°C-55°C, the reaction time to be 3-5h, and filtering after the reaction;
[0010] S3: Drying the sample obtained in step S2;
[0011] S4: placing the dried sample in a high-temperature furnace controlled with carbon dioxide or air atmosphere and calcining it to obtain magnesium oxide thermochemical heat storage material;
[0012] The microstructure of the magnesium oxide thermochemical heat storage material is a coral-like structure composed of nanoparticles.
[0013] The magnesium salt can be magnesium chloride hexahydrate or magnesium nitrate, and the carbonate can be potassium carbonate or sodium carbonate. Because of the reaction chemical formula in the MgO / MgCO3 system, the molar ratio of the magnesium precursor to the carbonate is the same or the carbonate is slightly excessive (for example, within 1.1 times or 1.2 times) to allow the magnesium precursor to fully react. The magnesium salt is preferably magnesium chloride hexahydrate (MgCl2·6H2O). Because the mining of salt lakes is accompanied by the byproducts of lithium and potassium extraction from salt lakes, MgCl2·6H2O accumulates in large quantities, which not only causes the soil salinization near the salt lake to intensify, but also causes a large amount of magnesium resource waste, which is not conducive to the long-term and effective development of the salt lake industry. Therefore, the present invention preferably selects MgCl2·6H2O as a magnesium source to achieve effective utilization of solid waste.
[0014] Preferably, stirring is maintained during the reaction in step S2. For example, the reaction can be carried out on a magnetic stirrer. The action of maintaining stirring during the reaction can increase the reaction efficiency of magnesium carbonate.
[0015] Preferably, in step S3, the sample obtained in step S2 is placed in an oven at 120° C. and dried for 12 hours.
[0016] Preferably, in step S4, the temperature is raised to the calcination temperature at a heating rate of 5°C / min, the calcination temperature is 370-380°C, and the calcination time is 2.5-3.5h.
[0017] Based on the same inventive concept, the present invention provides a magnesium oxide thermochemical heat storage material, and the magnesium oxide thermochemical heat storage material is obtained by the above-mentioned preparation method.
[0018] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:
[0019] The present invention obtains a magnesium oxide thermochemical heat storage material having a coral-like microstructure composed of nanoparticles by controlling the reaction temperature and reaction time of a magnesium salt solution and a carbonate, and controlling the atmosphere during calcination, so that the contact area between CO2 and MgO can be effectively increased during the heat energy release and storage process of the heat storage material, thereby improving the reaction rate.
[0020] The MgO thermochemical energy storage material prepared by the present invention has low crystallinity at the (111)(200)(220)(311) and (222) crystal planes, has more crystal plane defects, is more active, and has a faster reaction rate.
[0021] The magnesium source of the present invention is derived from solid waste of salt lakes. On the one hand, the solid waste can be recycled and reused to reduce the waste of magnesium resources. On the other hand, the MgO product can be used as a new generation of thermal energy storage material to increase the utilization rate of residual heat and waste heat. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the MgO-55°C-3h-CO2 energy storage material prepared in Example 1 of the present invention;
[0023] Figure 2 This is a scanning electron microscope image of the MgO-25°C-3h-CO2 energy storage material prepared in Comparative Example 1 of the present invention;
[0024] Figure 3 XRD diffraction patterns of magnesium oxide energy storage materials prepared in Examples 1-2 and Comparative Examples 1-2 of the present invention;
[0025] Figure 4 The energy storage density curves of the magnesium oxide energy storage materials prepared in Examples 1-5 and Comparative Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0026] The following is a further detailed description of a magnesium oxide thermochemical heat storage material and a preparation method thereof proposed by the present invention in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description.
[0027] The energy storage material obtained in the following examples is named MgO-ABC, A is the reaction temperature, B is the reaction time, and C is the calcination atmosphere.
[0028] Example 1
[0029] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-3h-CO2 for subsequent use.
[0030] The microscopic morphology and crystal structure analysis of MgO-55℃-3h-CO2 prepared in this example were performed. Figure 1 and Figure 3As shown, the MgO thermochemical energy storage material prepared by this temperature program presents a coral-like structure composed of nanoparticles, which can effectively increase the contact area between CO2 and MgO and improve the reaction rate during the process of thermal energy release and storage; taking the strongest diffraction peak of the (200) crystal plane with a 2θ angle of 42.9° as a reference, the MgO prepared by stirring at 55°C for 3 hours and calcining in a CO2 atmosphere has low crystallinity and exists more defects, that is, the higher the activity, the faster the reaction rate.
[0031] Then, a thermogravimetric analyzer was used to test the energy storage density of the MgO-55℃-3h-CO2 thermochemical energy storage material. 10 mg of MgO-55℃-3h-CO2 was weighed and placed in an alumina crucible and placed in a thermogravimetric analyzer; pure N2 was introduced into the thermogravimetric analyzer at a gas flow rate of 50 mL / min, and the temperature was raised to 350℃ at a heating rate of 10℃ / min at room temperature for 10 minutes to remove moisture and impurity gases; the gas was switched to a mixture of CO2 and N2 (40 vol% CO2 and 60 vol% N2 mixed atmosphere, flow rate of 50 mL / min), and the temperature was kept at 350℃ for 120 minutes (30 minutes for the cyclic stability test).
[0032] According to the mass change data during the test, the energy storage density of MgO-based thermochemical energy storage materials is calculated:
[0033]
[0034] The test structure of energy storage density is as follows: Figure 4 As shown, the energy storage density for 120 minutes is 416.9 kJ / kg.
[0035] Example 2
[0036] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in an air atmosphere (Air) and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-3h-Air for subsequent use.
[0037] The crystal structure of MgO-55℃-3h-Air prepared in this example is analyzed. Figure 3As shown, taking the strongest diffraction peak of the (200) crystal plane as a reference, the MgO prepared by stirring at 55°C for 3 hours and calcining in an Air atmosphere has low crystallinity and more defects, that is, the higher the activity, the faster the reaction rate.
[0038] Then, the energy storage density of MgO-55°C-3h-Air in this embodiment was tested using a thermogravimetric analyzer in the same testing method as in Example 1. The results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 396.0 kJ / kg.
[0039] Example 3
[0040] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 5 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in an air atmosphere (Air) and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-5h-Air for subsequent use.
[0041] The energy storage density of MgO-55℃-5h-Air in this embodiment was tested by the same test method as in Example 1 using a thermogravimetric analyzer. The results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 381.2 kJ / kg.
[0042] Example 4
[0043] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 5 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-5h-CO2 for subsequent use.
[0044] The energy storage density of MgO-55℃-5h-CO2 in this embodiment was tested using a thermogravimetric analyzer in the same test method as in Example 1. The results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 355.4 kJ / kg.
[0045] Example 5
[0046] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 30°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-30°C-3h-CO2 for subsequent use.
[0047] The energy storage density of MgO-30℃-3h-CO2 in this embodiment was tested by the same test method as in Example 1 using a thermogravimetric analyzer. The results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 333.5 kJ / kg.
[0048] In order to verify whether other preparation methods can produce the same effect, the following comparative experiments were also carried out:
[0049] Comparative Example 1:
[0050] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 25°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-25°C-3h-CO2 for subsequent use.
[0051] Thermogravimetric analysis instrument was used to test the energy storage density of MgO thermochemical energy storage material. 10 mg of material was weighed and placed in an alumina crucible, and placed in a thermogravimetric analyzer; pure N2 was introduced into the thermogravimetric analyzer at a gas flow rate of 50 mL / min, and the temperature was raised to 350°C at a heating rate of 10°C / min at room temperature for 10 minutes to remove moisture and impurity gases; the gas was switched to a mixture of CO2 and N2 (40 vol% CO2 and 60 vol% N2 mixed atmosphere, flow rate of 50 mL / min), and the temperature was kept at 350°C for 120 minutes (30 minutes for cyclic stability test).
[0052] The crystal structure of MgO-25℃-3h-CO2 prepared in Comparative Example 1 was analyzed. Figure 2 As shown, with the strongest diffraction peak of the (200) crystal plane as a reference, the MgO prepared by stirring at 25°C for 3 hours and calcining in a CO2 atmosphere has a higher crystallinity, a more complete crystal surface, a lower activity, and a slow reaction rate. The test results of energy storage density are shown in Figure 4 As shown, the energy storage density for 120 minutes is 200.7 kJ / kg.
[0053] Comparative Example 2:
[0054] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 70°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-70°C-3h-CO2 for subsequent use.
[0055] The crystal structure of MgO-70℃-3h-CO2 prepared in Comparative Example 2 was analyzed. Figure 2 As shown, taking the strongest diffraction peak of the (200) crystal plane as a reference, the MgO prepared by stirring at 70°C for 3 hours and calcining in a CO2 atmosphere has a higher crystallinity, a sharper peak shape, and fewer defects, that is, the lower the activity, the slower the reaction rate.
[0056] The energy storage density of MgO-70℃-3h-CO2 in this comparative example was tested using a thermogravimetric analyzer in the same test method as in comparative example 1. The test results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 240.1 kJ / kg.
[0057] Comparative Example 3
[0058] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 1 hour, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-1h-CO2 for subsequent use.
[0059] The energy storage density of MgO-55℃-1h-CO2 in this comparative example was tested by the same test method as in comparative example 1 using a thermogravimetric analyzer. The results are as follows: Figure 3 As shown, the energy storage density for 120 minutes is 272.3 kJ / kg.
[0060] Comparative Example 4
[0061] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 7 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a CO2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-7h-CO2 for subsequent use.
[0062] The energy storage density of MgO-55℃-7h-CO2 in this comparative example was tested by the same test method as in comparative example 1 using a thermogravimetric analyzer. The results are as follows: Figure 4 As shown, the energy storage density can reach 297.4 kJ / kg in 120 minutes.
[0063] Comparative Example 5
[0064] Weigh 12.71 g of MgCl2·6H2O and 8.64 g of K2CO3 into beakers respectively, add 100 mL of deionized water and stir to form a solution; place the beaker containing the K2CO3 solution on a magnetic stirrer and pour in the pre-prepared MgCl2·6H2O solution, stir at 55°C for 3 hours, and filter after the reaction; put the stirred sample into a 120°C oven and dry it for 12 hours; put the dried sample into a tubular furnace in a N2 atmosphere and calcine at 375°C for 180 min to obtain MgO thermochemical energy storage material (heating rate 5°C / min); put the cooled sample into an agate mortar and grind it into powder, put it into a sealed bag and seal it, named MgO-55°C-3h-N2 for subsequent use.
[0065] The energy storage density of MgO-55℃-3h-N2 in this comparative example was tested by the same test method as in comparative example 1 using a thermogravimetric analyzer. The results are as follows: Figure 4 As shown, the energy storage density for 120 minutes is 321.1 kJ / kg.
[0066] The reaction conditions and energy storage densities of Examples 1-5 and Comparative Examples 1-5 are summarized in the following table:
[0067]
[0068] It can be concluded from the above-mentioned Examples 1-5 and Comparative Examples 1-5 that the present invention prepares a coral-like structure composed of nanoparticles by precisely controlling the reaction temperature and reaction time of the magnesium salt solution and the carbonate solution, as well as precisely controlling the calcination atmosphere, which can effectively increase the contact area between CO2 and MgO and improve the reaction rate during the heat release and storage process; and the magnesium oxide thermochemical energy storage material prepared by the method provided by the present invention has low crystallinity on the (111)(200)(220)(311) and (222) crystal planes, has more crystal plane defects, is more active, and has a faster reaction rate, thereby obtaining a higher energy storage density.
[0069] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.
Claims
1. A method for preparing a magnesium oxide thermochemical heat storage material, characterized in that: The following steps are involved: S1: weigh magnesium salt and carbonate, and add deionized water to dissolve them respectively to form a magnesium salt solution and a carbonate solution; S2: adding the magnesium salt solution to the magnesium carbonate solution, and controlling the reaction temperature to be 30°C-55°C, the reaction time to be 3-5h, and filtering after the reaction; S3: Drying the sample obtained in step S2; S4: placing the dried sample in a high-temperature furnace controlled with carbon dioxide or air atmosphere and calcining it to obtain magnesium oxide thermochemical heat storage material; The microstructure of the magnesium oxide thermochemical heat storage material is a coral-like structure composed of nanoparticles.
2. The method for preparing the magnesium oxide thermochemical heat storage material according to claim 1, characterized in that: In step S2, stirring is maintained during the reaction process.
3. The method for preparing the magnesium oxide thermochemical heat storage material according to claim 1, characterized in that: In step S3, the sample obtained in step S2 is placed in an oven at 120° C. and dried for 12 hours.
4. The method for preparing the magnesium oxide thermochemical heat storage material according to claim 1, characterized in that: In the step S4, the temperature is raised to the calcination temperature at a heating rate of 5°C / min, the calcination temperature is 370-380°C, and the calcination time is 2.5-3.5h.
5. The method for preparing the magnesium oxide thermochemical heat storage material according to claim 1, characterized in that: The magnesium salt is MgCl2·6H2O.
6. A magnesium oxide thermochemical heat storage material, characterized in that: The magnesium oxide thermochemical heat storage material is obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Cited By
METHOD FOR PRODUCING AND USING HEAT-SAVING AGENT OF MgAlZr-LDH TYPE INTERCALATED WITH ORGANIC MOLECULES
RU2870665C1